Sacroiliitis in Systemic Lupus Erythematosus Revisited - Neslihan YILMAZ,; Ayten YAZICI,; Banu ÖZULU TÜRKMEN,; Işık KARALOK,; Şule YAVUZ, (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the prevalence of inflammatory back pain (IBP) and sacroiliitis in a systemic lupus erythematosus (SLE) population as well as the association between IBP and the frequency of human leukocyte antigen B27 (HLA-B27). Patients and methods: The study included 281 SLE patients (16 males, 265 females; mean age 39.9±11.9 years; range, 20 to 69 years) and 100 healthy controls (HCs) (2 males, 98 females; mean age 41.2±10.1 years; range, 19 to 64 years). Participants were administered a five-item Assessment of SpondyloArthritis international Society-IBP questionnaire. Patients and controls with IBP underwent detailed clinical and laboratory examinations to detect sacroiliitis. Radiographic evaluations were performed by a blinded rheumatologist and radiologist. Interobserver reliability was assessed with Cohen’s kappa test. Results: According to the questionnaire, IBP was present in 46 SLE patients (46/281; 16.3%) whereas none of the HC had IBP (p<0.001). In radiological assessment, 22 SLE patients (7.8%) had sacroiliitis detected by conventional X-ray and/or magnetic resonance imaging. Only one SLE patient with sacroiliitis had HLA-B27. Conclusion: Our study showed that IBP is increased in SLE patients and IBP in SLE is not associated with HLA-B27.